Letter - Max Winter Limited; Winter, Fred
1939-12-28 038-0051-003 TELEPHONE: HOLBORN 8108. TELEGRAMS: "CORUNDSTAR - LONDON." FRED WINTER MAX WINTER LTD. DIRECTORS: HERMANN STERN (GERMAN ORIG.), FRED WINTER (GERMAN ORIG.), MAX WINTER 34, RUE DROUOT. PARIS 101/102, HATTON GARDEN, LONDON, E.C.1. ptivate & confidential 28th DECEMBER 1939 Mr Hunt SPANISH REFUGEE COMMITTEE W 1 Dear Sir, I send you herewith a letter from Mr Gallut, a spanish Gentleman: before the War I gave some assistance to spanish refugees, recommended to me by the Comite Socialiste in Paris, but now, in War's time and as a German Jew, I can hardly do anything in such matters by reasons, which you of course will easily understand. I should therefore be much obliged to you to take this matter into your hands. Thanking you, I remain, dear Sir, yours sincerely Fred Winter 292/946/38/51(III)